COGNITION DISORDERS IN HYPERTENSIVE PATIENTS OF OLDER AGE AND SENILE - N. V. Sharashkina; V. S. Ostapenko; О. N. Tkacheva; N. К. Runikhina; Yu. V. Kotovskaya; E. A. Mkhitarian; S. N. Lysenkov (Кардиоваскулярная терапия и профилактика)
Aim. To assess cognitive status  of the older age patients  with arterial hypertension, in outpatient setting.Material and methods. Totally, 356 patients included, age 74,9±6,1 y., 80,4% females. For cognition assessment before and after the treatment, neuropsychological test was done, with MMSE — short scale of psychic status assessment, drawing test; literal and categoric associations  test.Results. In the  group  <80  y.o. the  prominence  of MMSE disorders correlated  with blood pressure values (BP): for systolic BP (r=-0,22, р=0,0003), for diastolic BP (r=-0,13, p=0,03), i.e. in higher BP patients there were lower points in cognition scale by Spearman  correlation. In the group ≥80 y. both correlations were non-significant, for systolic BP (r=-0,05, p=0,64), and for diastolic BP (r=-0,13, р=0,25).Conclusion. In older age and senile patients with arterial hypertension there should be differential approach  to BP management according  to the age and cognition disorders, complex approach to treatment in these patients might prevent further worsening of cognitive decline.